Stachydrine Ameliorates Cardiac Fibrosis Through Inhibition of Angiotensin II/Transformation Growth Factor β1 Fibrogenic Axis - Liu, Xiao; Shan, Xiaoli; Chen, Huihua; Li, Zan; Zhao, Pei; Zhang, Chen; Guo, Wei; Xu, Ming; Lu, Rong (Frontiers in Pharmacology, 2019)
Cardiovascular diseases, the leading cause of death worldwide, are tightly associated with the pathological myocardial fibrosis. Stachydrine (Sta), a major active compound in Chinese motherwort Leonurus heterophyllus, was reported to effectively attenuate cardiac fibrosis, but the cellular and molecular mechanism remains unclear. In this study, the anti-fibrotic effect of Sta and mechanism underlying were explored in a mouse model of pressure overload and AngII stimulated cardiac fibroblasts (CFs). Mice were randomly divided into sham, transverse aorta constriction with saline (TAC+Sal), TAC with telmisartan (TAC+Tel), and TAC with Sta (TAC+Sta) groups. Cardiac morphological and functional changes were evaluated by echocardiography and histological methods, and the molecular alterations were detected by western blotting. Primary cultured neonatal mouse CFs were treated with or without angiotensin II (AngII, 10−7 M), transformation growth factor β1 (TGFβ1, 10 ng/mL), and different dosage of Sta (10−6–10−4 M) for up to 96 h, and cell proliferation, cytotoxicity, morphology and related signals were also detected. The in vivo results revealed that TAC prominently induced cardiac dysfunction, left ventricular dilation, myocardial hypertrophy, and elevated myocardial collagen deposition, accompanied with increased fibrotic markers including α-smooth muscle actin (α-SMA) and periostin. However, Sta treatment partially reversed cardiac morphological and functional deteriorations, and significantly blunted cardiac fibrosis as well as Tel. Increments of myocardial angiotensinogen (AGT), angiotensin converting enzyme (ACE), AngII type 1 receptor (AT1R), and TGFβ1 transcripts, together with increased protein levels of ACE and AngII, after TAC were dramatically down-regulated by Sta treatment. Coincidently, in vitro experiments demonstrated that AngII stimulation in CFs led to up-regulation of AT1R and TGFβ1, and therefore promoted CFs trans-differentiating into hyper-activated myocardial fibroblasts (MFs) as evidenced by increased cell proliferation, collagen and fibrotic makers. On the contrary, Sta potently down-regulated but not directly inhibited AT1R, suppressed TGFβ1 production, and the pro-fibrotic effect of AngII in CFs. Moreover, activation of TGFβ1/Smads signal in the fibrotic process were observed both TAC model and in AngII stimulated CFs, which were also notably blunted by Sta. However, Sta failed to abolish the activation of CFs triggered by TGFβ1. Taken together, it was demonstrated in this study that Sta suppressed ACE/AngII/AT1R-TGFβ1 profibrotic axis, especially on the de novo production of AngII via down-regulating AGT/ACE and AT1R, and therefore inactivated CFs and blunted MFs transition, which ultimately prevented cardiac fibrosis.